The effect of online customer reviews on buying interest through customer trust in e-commerce - Maura Safira; Alimuddin Rizal Riva’i (Institute of Computer Science (IOCS), 2024)
This research aims to test and analyze the effect of online customer reviews on buying interest through customer trust in e-commerce. The population in this research are users and buyers of e-commerce sites. The sampling technique used was purposive sampling, where the researchers took a sample of 108 respondents with the criteria that the respondents had bought and made purchases at least twice in 3 months in e-commerce. Data collection was carried out by distributing questionnaires to respondents using Google Forms. Data analysis in this research used multiple linear regression with the help of the SPSS 23 program. The results of this research indicate that online customer reviews have a positive and significant effect on buying interest through customer trust. Online customer reviews have a more dominant influence on buying interest than customer trust. This research only tests and analyzes one independent variable, namely, online customer reviews. Therefore, it is hoped that future research can add other variables related to increasing buying interest and customer trust